Atrial fibrillation in pigs induces left atrial endocardial transcriptional remodelling - Cerveró, Jorge; Segura, Víctor; Macías, Alfonso; Gavira, Juan José; Montes, Ramón; Hermida, José (Thrombosis and Haemostasis, 2012)
The leading cause of cardioembolic stroke is atrial fibrillation (AF), which predisposes to atrial thrombus formation. Although rheological alterations promote a hypercoagulable environment, as yet undefined factors contribute to thrombogenesis. The role of the endocardium has barely been explored. To approach this topic, rapid atrial pacing (RAP) was applied in four pigs to mimic A F. Left and right endocardial cells were isolated separately and their gene expression pattern was compared with that of four control pigs. The AF-characteristic rhythm disorders and endothelial nitric oxide synthase down-regulation were successfully reproduced, and validated RAP to mimic A F. A change was observed in the transcriptomic endocardial profile after RAP: the expression of 364 genes was significantly altered (p<0.01), 29 of them having passed the B>0 criteria. The left atrial endocardium [325 genes (7 genes, B>0)] was largely responsible for such alterations. Blood coagulation, blood vessel morphogenesis and inflammatory response are among the most significant altered functions, and help to explain the activation of coagulation observed after RAP: D-dimer, 0.49 (1.63) vs. 0.23 (0.24) mg/l [median (interquartile range)] in controls, p=0.02. Furthermore, three genes directly related to thrombotic processes were differentially expressed after RAP: FGL2 [fold change (FC)=0.85; p=0.007], APLP2 (FC=-0.47; p=0.005) and ADAMTS-18 (FC=-0.69; p=0.004). We demonstrate for the first time that AF induces a global expression change in the left atrial endocardium associated with an activation of blood coagulation. The nature of some of the altered functions and genes provides clues to identify new therapeutic targets.
Keywords: Animals models; endothelial cells; vascular remodelling; heart; gene expression